Profile of PKS and NRPS Gene Clusters in the Genome of Streptomyces cellostaticus NBRC 12849T - Hisayuki Komaki; Tomohiko Tamura (Fermentation, 2023)
Polyketides and nonribosomal peptides are major secondary metabolites in members of the genus Streptomyces. Streptomyces cellostaticus is a validly recognized species and the type strain produces cellostatin. However, little is known about whether it has the potential to produce diverse polyketides and nonribosomal peptides. Here, we sequenced the whole genome of S. cellostaticus NBRC 12849T and surveyed polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) gene clusters in the genome. The genome encoded 12 PKS, one NRPS and eight hybrid PKS/NRPS gene clusters. Among the 21 gene clusters, products of 10 gene clusters were annotated to be an annimycin congener, fuelimycins, lankamycin, streptovaricin, spore pigment, flaviolin, foxicin, blasticidin, lankacidin and an incarnatapeptine congener via our bioinformatic analysis. Although the other clusters were orphan and their products were unknown, five of them were predicted to be compounds derived from two independent diketides, a tridecaketide, a triketide and a tetraketide with a cysteine residue, respectively. These results suggest that S. cellostaticus is a source of diverse polyketides and hybrid polyketide/nonribosomal peptides, including unknown and new secondary metabolites.